1838
DOI: 10.5962/bhl.title.62140
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of fishes, amphibians, & reptiles, or monocardian animals

Abstract: CLASSIFICATION OF MONOCARDIAN ANIMALS. appearance they then exhibit, few will study, and still fewer will collect them.Hence the ichthyologist has much greater difficulties to contend with, in regard to materials, than he would experience in any other division, of the Vertebrata, while he finds himself totally at a loss for that information on their natural habits, " their lives, and their loves," which gives such a charm to the history of other animals, and excites such a popular interest with the generality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

1966
1966
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 0 publications
0
45
0
2
Order By: Relevance
“…Berry and Baldwin (1966) and Matsuura (1981) observed that, the three species of Swainson (1839) i.e. Canthidermis angulosus (Quoy and Gaimard, 1825), Canthidermis gaimardii (Swainson, 1839) and Canthidermis oculatus (Gray, 1830) are synonyms of Canthidermis maculata (Bloch, 1786). They also established that Balistes maculata (Gmelin, 1789) and Balistes aureolus (Richardson, 1845) of Gunther (1870) is a synonym of Balistes maculatus (Bloch, 1786).…”
Section: Discussionmentioning
confidence: 99%
“…Berry and Baldwin (1966) and Matsuura (1981) observed that, the three species of Swainson (1839) i.e. Canthidermis angulosus (Quoy and Gaimard, 1825), Canthidermis gaimardii (Swainson, 1839) and Canthidermis oculatus (Gray, 1830) are synonyms of Canthidermis maculata (Bloch, 1786). They also established that Balistes maculata (Gmelin, 1789) and Balistes aureolus (Richardson, 1845) of Gunther (1870) is a synonym of Balistes maculatus (Bloch, 1786).…”
Section: Discussionmentioning
confidence: 99%
“…Four years before Bonaparte, Agassiz (1834) had already separated the Cyprinodonts and the Cyprinidae, removing Anableps Scopoli, Poecilia, Lebias, Fundulus, Mollienesia, and Cyprinodon to a new family "Cyprinodontes". Swainson (1838) placed Poeciliinae as a subfamily of Cobitidae. Gill (1857) adopted the name Cyprinodontes and later (Gill, 1865;1894) employed Poeciliidae.…”
Section: P R O O F Smentioning
confidence: 99%
“…Order PERCIFORMES Bleeker, 1859(sensu Patterson, 1964) Suborder PERCOIDEI sensu Bleeker, 1859 (sensu Nelson, 2006) Family "SERRANIDAE" Swainson, 1839 Genus and species indeterminate Referred Material. IGM 4550 (Figure 6), specimen from the División del Norte quarry (= Locality-IGM 3869).…”
Section: Systematic Paleontologymentioning
confidence: 99%